Analisis Struktural dalam Novel “Jelatik” Karya Riki Utomi - Rani Putri Khanza; Asnawi Asnawi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Literature in general is the creation of poets to express ideas, feelings and dreams in the process of creating beautiful strings of words or arranging strings of inappropriate words. One of the literary theories used to dissect or analyze a literary work and which will be the main focus in this article is Structural Theory. The data analysis technique in this research uses qualitative data analysis techniques. The collection techniques used are observation, reading techniques and note-taking techniques. Observation in research is a data collection method that involves direct observation of an event. This observation process can involve paying attention to elements such as plot, characters, themes, writing style, narrative structure, and other aspects that influence the reading experience and understanding of the novel Jelatik by Riki Utomi. Structuralism analysis of the novel